2005
DOI: 10.1360/02yd0464
|View full text |Cite
|
Sign up to set email alerts
|

Paleoearthquake rupture behavior and recurrence of great earthquakes along the Haiyuan fault, northwestern China

Abstract: It is generally accepted that crustal earthquakes are caused by sudden displacement along faults, which rely on two primary conditions. One is that the fault has a high degree of synergism, so that once the stress threshold is reached, fault segments can be connected rapidly to facilitate fast slip of longer fault sections. The other is sufficient strain accumulated at some portions of the fault which can overcome resistance to slip of the highstrength portions of the fault. Investigations to such processes wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 18 publications
1
70
0
1
Order By: Relevance
“…GPS measurements of 3-5 mm/yr (Zhang et al, 2004;Gan et al, 2005) corroborate well with the geological rate. The recurrence interval is reported to be in a thousand year cycle, which is almost the consensus from previous paleoseismic studies (Zhang et al, 1988b;Gaudemer et al, 1995;Liu et al, 1995;Ran et al, 1997;Ran and Deng, 1998;Min et al, 2001;Zhang et al, 2005;Liu-Zeng et al, 2007), among which Zhang et al (2005) proposed synthesis results from 19 trenches on the Haiyuan fault. Geological studies of the 1920 Haiyuan Ms 8.5 earthquake began in 1921, but 1:50,000 scale geological and active fault mapping was not accomplished until the 1980s.…”
Section: Geological Backgroundsupporting
confidence: 78%
See 1 more Smart Citation
“…GPS measurements of 3-5 mm/yr (Zhang et al, 2004;Gan et al, 2005) corroborate well with the geological rate. The recurrence interval is reported to be in a thousand year cycle, which is almost the consensus from previous paleoseismic studies (Zhang et al, 1988b;Gaudemer et al, 1995;Liu et al, 1995;Ran et al, 1997;Ran and Deng, 1998;Min et al, 2001;Zhang et al, 2005;Liu-Zeng et al, 2007), among which Zhang et al (2005) proposed synthesis results from 19 trenches on the Haiyuan fault. Geological studies of the 1920 Haiyuan Ms 8.5 earthquake began in 1921, but 1:50,000 scale geological and active fault mapping was not accomplished until the 1980s.…”
Section: Geological Backgroundsupporting
confidence: 78%
“…The Haiyuan fault then changed to a major left-lateral strike-slip fault in the late Pliocene or early Pleistocene (Burchfiel et al, 1991). Over shorter time scales, researchers have focused on active tectonics studies involving active fault mapping (IGCEA, NBCEA, 1990), fault slip rate evaluation (Zhang et al, 1988a;Lasserre et al, 1999;Li et al, 2009), paleoseismology (Zhang et al, 1988b;Gaudemer et al, 1995;Liu et al, 1995;Ran et al, 1997;Ran and Deng, 1998;Min et al, 2001;Zhang et al, 2005;Liu-Zeng et al, 2007), and the analysis of the 1920 coseismic surface rupture zone (Song et al, 1983;Zhang et al, 1987). Slip rates have also been reported based on modern surveys involving interferometric synthetic aperture radar (InSAR), global positioning system (GPS), and LiDAR (Wang et al, 2003;Gan et al, 2005;Liu et al, 2013;Chen et al, 2014).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Individual fault strands mostly trend N60°-65°W and intersect the average strike of fault zone at about 15°, except for F 1 . The Haiyuan fault can be divided into three segments according to fault geometry, geomorphology, and paleoseismology [Zhang et al, 2003].…”
Section: Tectonic Setting and Geometric Pattern Of The Haiyuan Faultmentioning
confidence: 99%
“…Paleoseismological studies conducted at Shaomayin and another site (Caiyuan, about 15 km east of Shaomayin site) by Zhang et al [1988bZhang et al [ , 2003 revealed that the earthquake recurrence interval along the Haiyuan fault is greater than 800 years, and possibly 800 to 1400 years. Ran et al [1997] excavated a series trenches to study horizontal displacement associated with paleoearthquakes only 300 m east of our Gaowanzi site.…”
Section: Comparison With Gps Interferometric Aperture Radar and Palmentioning
confidence: 99%
“…However, in many real applications, non-spatial attributes are of most concern to users [17][18][19][20]. In a spatial database with non-spatial attributes, data points that are similar to each other in their non-spatial attributes may be scattered geometrically.…”
mentioning
confidence: 99%